at-Tahdiyāt fī Taʽlīm al-Aşwāt al-ʽArabiyah li ad-Dārisīn al-Indūnīsiyīn wa Hulūliha - Isra Hayati Darman; Rani Ismil Hakim; Halimatus Sa`diyah; Ahmed Abdulkafi Almurib (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2025)
مستخلص البحث: يوجد العديد من الأخطاء في نطق الأصوات العربية لدى الطلاب الجامعي. ولا يقتصر على الطلاب الخريجين من المدارس الثانوية أو المدارس المهنية، بل يشمل أيضاً بعض الطلاب الخريجين من المدارس الإسلامية. تهدف هذه الدراسة إلى تحليل التحديات التي يواجهها الدارسون الإندونيسيون في تعلم الأصوات العربية ولمعرفة الحلول المقترحة لمواجهتها. والمنهج المستخدم في هذا البحث هو الوصفي التحليلي بدراسة المصادر والمراجع من كتب ومقالات علمية. وتشير نتائج البحث إلى أن من التحديات في تعلم أصوات اللغة العربية هي: التحديات من جهة المشكلات الصوتية، والتحديات من قبل الدارسين، والتحديات من قبل المدرسين. وأما من الحلول لمواجهة هذه التحديات منها: التدريبات المستمرة والتركيز على الأصوات المعينة، واعطاء التشجيعات للدارسين، واستعمال الوسائل الرقمية والزكاء الإصطنائي للتدريبات في النطق الأصوات العربية، وتصميم المواد تعليم الأصوات على دراسة تقابلية، وعلى المدرسين أن يفهموا خصائص ومميزات الاصوات العربية، وأن يرتكز على تعليم الأصوات قبل تعليم المفردات والقواعد. الكلمات الأساسية : التحديات، الحلول، تعليم الأصوات Abstract: There are some errors in the pronunciation of Arabic sounds among university students. These errors are not limited to graduates of general or vocational high schools but also include some graduates of Islamic schools. This study aims to analyze the challenges faced by Indonesian learners in learning Arabic phonetics and identify solutions to address these challenges. The method used in this research is descriptive-analytical, involving the review of sources and references from books and scientific articles. The result indicate that the challenges in learning Arabic phonetics include phonetic-related issues, challenges from the learners’ side, and challenges from the teachers’ side. Proposed solutions to these challenges include intensive practice and focus on specific sounds, providing motivation to learners, utilizing digital tools and artificial intelligence for pronunciation training, designing phonetic learning materials based on contrastive studies, and ensuring that teachers understand the characteristics and features of Arabic sounds, and phonetic teaching be prioritized before vocabulary and grammar teaching. Keywords: Challenges, Solution, Phonetic teaching